FORMATION OF NANO-AND ULTRAFINE PALLADIUM POWDERS IN THE PRESENCE OF «RED-OX»SYSTEM«TITANIUM (III) - TITANIUM (IV)» - Bayeshov A.B.; Gaipov T.E.; Bayeshova A.K. (Academic Scientific Journal of Chemistry, 2020)
The results of studies on the processes of obtaining ultra - and nanodispersed palladium powders from sulphate solutions by a combined chemical and electrochemical method in the presence of a "red-ox" system of titanium (III) - titanium (IV) are presented. It has been shown that when a titanium trivalent sulphate solution is added to a solution containing palladium (II) ions, palladium ions are immediately reduced to elemental state to form a nanodispersed powder. The completeness of the above-mentioned oxidizing-reducing reactions is established on the basis of calculating the equilibrium constant (K), which is 1034 and indicates that trivalent titanium ions completely reduce palladium ions to elemental state. Effect of initial concentration of palladium ions on amount of formed palladium powder with addition of equivalent amount of trivalent titanium ions is investigated. According to the authors, upon reduction of palladium ions, elemental palladium is formed in the atomic state, and over time, the atoms begin to combine with each other. Subsequently, atomic particles are combined into colloidal particles. It has been found that in the absence of coagulants, the colloidal palladium solution is stable for 2- 3 hours, and in the presence of gelatin, the stability increases and remains for 36 hours. It was shown that in all experiments powders with spherical particles are formed, the average sizes of which range from 0.116-0.240 microns. Based on the results of the presented studies, a new technology for producing ultra - and nano-sized palladium powders is proposed.